Size Matters: Cerebral Volume Influences Sex Differences in Neuroanatomy - Leonard, Christiana M.; Towler, Stephen; Welcome, Suzanne; Halderman, Laura K.; Otto, Ron; Eckert, Mark A.; Chiarello, Christine (Cerebral Cortex (New York, NY), 2008)
Biological and behavioral differences between the sexes range from obvious to subtle or nonexistent. Neuroanatomical differences are particularly controversial, perhaps due to the implication that they might account for behavioral differences. In this sample of 200 men and women, large effect sizes (Cohen's d > 0.8) were found for sex differences in total cerebral gray and white matter, cerebellum, and gray matter proportion (women had a higher proportion of gray matter). The only one of these sex differences that survived adjustment for the effect of cerebral volume was gray matter proportion. Individual differences in cerebral volume accounted for 21% of the difference in gray matter proportion, while sex accounted for an additional 4%. The relative size of the corpus callosum was 5% larger in women, but this difference was completely explained by a negative relationship between relative callosal size and cerebral volume. In agreement with Jancke et al., individuals with higher cerebral volume tended to have smaller corpora callosa. There were few sex differences in the size of structures in Broca's and Wernicke's area. We conclude that individual differences in brain volume, in both men and women, account for apparent sex differences in relative size.
Keywords: neurosciences